Lazer na escola: descompromisso compromissado - Awad, Hani Zehdi Amine (2002)
This study had as a purpose to find out the concept of the students' parents of the Elementary Teaching of the State School Unidade Pólo in Maringá city, Paraná State about leisure, school life and social mobilization. We also tried to identify the profile of the students' parents related to: sex, profession, number of children, and the grades their children are in at school. This study was realized based on a descriptive character. The research was at the State School Unidade Pólo in Maringá- PR. In that school we worked with all the students’ parents of the Elementary Teaching, who attended the activities we developed on Saturdays and Sundays along the months of October and November, with a total of 50 parents involved. We used a mixed questionnaire with fifteen questions as a tool to get the necessary data. There were eleven subjective questions and three objective ones which were given to 41 parents that participated in the leisure activities developed on the weekends. Besides, we also used an observation card to emphasize some speeches and situations occurred in the leisure activities development at school. In the first chapter, we discussed the leisure and how it is related to work, trying to understand the different forms that the leisure assumed historically, from the Industrial Revolution to the current days. In the second chapter, we debated the understanding of what social movements are and the school as a space to implement these movements. The third chapter shows the discussions and the results of the research. We verified, based on the collected data and the accomplished analyses, that the students' parents of the Elementary Teaching present the following profile: 78% are mothers, 65,8% have children between the first and fourth grades, and the most frequent profession was classified as “others” with 34,1%, the second most frequent was “housewife” with 29,3%. We could also observe that the concept most of the parents have about leisure, school life and social mobilization is superficial, fragmented, and it does not take into consideration the social, economical, and political aspects that involve these social phenomena. Thus, we delimited what leisure is supported on the literature, on leisure, and work. This study realized that there are several studies and they present differences and similarities concerned to what leisure is. We observed that historically it has always been treated as a moment of complete lack of obligation, a freedom situation. There are some authors who disagree with the fact of discussing leisure by itself, so it should be associated to work. We revisited the historical processes of the theories that discuss the understanding of what social movements and the school are considering them as spaces toXI implement these movements. When the parents were asked about the importance of leisure, they answered it was very important for their lives. However, when these data were related to the found concept of leisure, we observed that what they think about the leisure and the importance they give to their families is incoherent. The leisure time the families should have during the week has been extended for the weekends. Most families are not members at clubs and the schools where they could practice these activities are closed, so they cannot do the leisure exercises. Regarding the levei of the parents' involvement with the daily school, we could notice that, at a first moment their participation is reasonable. When we observed the reasons presented by the parents, we noticed that they have not been concerned about the school organization, contents, and methods. Thus, the parents tend to assume a conformist role or just each son's individual verifier and the group struggle comes in a second stage. Regarding the parents' understanding about Social Mobilization, we could observe they understand Social Mobilization as collective actions of specific orders which result in the organization of a group of people, in order to achieve a common goal. This way, the idea the parents have about Social Mobilization is reactionary, since it attributes to the mobilizations either the re-balance function or the “normality” of the social system again and not the debate and overcoming of the established social order. Those data are crisis and school problems evidence that come to corroborate with our initial thesis which is the use of leisure activities to bring the families to school, as an agglutination form, and at the same time in the composition of an identity - politically centered - that allows the community participation to solve the problems presented by the school. The relationship school/ community can and must constitute a united and organized force on behalf of implementations against the established social order, starting with leisure.